"Slowly Becoming Sales Promotion Men?": Negotiating the Career of the Sales Representative in Britain, 1920s–1970s. (7th August 2015) - FRENCH, MIKE
Abstract : The commercial traveler, or traveling salesman, was an agent of commercialism and modernization as well as a stock character in British popular culture. To C. Wright Mills, salesmen faced particularly challenging demands to conform to managerial direction. This article examines how British salesmen negotiated their occupational identity during the twentieth century. Developments in marketing, corporate growth, and periods of war and recession all challenged salesmen's status and autonomy. These influences prompted a lengthy and recurring debate about how best to present, defend, and justify their work and identity. New marketing techniques and management systems evolved steadily, rather than producing sudden or uniform changes in the ways in which salesmen worked. Their culture of enterprise and individualism persisted, in part as it was shared by employers and managers. The impact of new marketing methods proved greatest in confectionery, tobacco, and other consumer goods trades as sales of branded, packaged goods expanded. Even then, salesmen contributed to shaping their work and occupational identity, proving unable to establish professional credentials and dividing over whether adopting trade union methods could improve their position.